2011
DOI: 10.1167/iovs.11-7878
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurement by Radio Wave Telemetry

Abstract: The WIT is well tolerated by the rabbit eye. Its measurements are reproducible and in close concordance with manometry. A downward IOP drift warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 24 publications
2
78
0
2
Order By: Relevance
“…Also, identification by several investigators of transparent and relatively inert plastics (polymethylmethacrylate, etc.) for the manufacturing of devices (particularly Stone and Herbert [78]), as well as the introduction of better surgical techniques at that time, resulted in improved keratoprosthesis (KPro) outcomes. Moreover, varied KPro designs were presented by a number of investigators in the early 1950s-virtually all presently used configurations were already suggested at that time (reviewed by Cardona [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Also, identification by several investigators of transparent and relatively inert plastics (polymethylmethacrylate, etc.) for the manufacturing of devices (particularly Stone and Herbert [78]), as well as the introduction of better surgical techniques at that time, resulted in improved keratoprosthesis (KPro) outcomes. Moreover, varied KPro designs were presented by a number of investigators in the early 1950s-virtually all presently used configurations were already suggested at that time (reviewed by Cardona [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Tele metric IOP measurement allows monitoring of IOP in patients who cannot be measured by current methods, such as patients with kera toprosthesis. A recent experimental study of telemetric IOP records used a wireless transducer implanted in rabbits after extracapsular lens extraction demonstrating concordance with direct manometry measures (42) . Further studies are necessary, however, to validate its use and safety in human eyes.…”
Section: Future Perspectivesmentioning
confidence: 83%
“…The implantable IOP sensor is three orders of magnitude smaller than commercially available devices 48,65 , minimizing the risks associated with implantation procedures as well as post surgery and long-term complications. We profiled dynamic changes of IOP in anesthetized rabbits for short-term (1 h) and in awake rabbits for long-term (4.5 months) periods, with an average accuracy of 0.29 mm Hg at a rate of 10 Hz over the physiologically interested range of 0-40 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Such measurements can only be obtained for up to 24 h because of side complications that accompany long-term use [41][42][43] . To overcome the aforementioned limitations, implants based on radio-frequency (RF) technologies have been used to monitor endovascular pressure 44 , intracranial pressure (ICP) 45,46 , and IOP [47][48][49][50][51][52][53][54][55][56][57][58] . The typical size of these implants ranges from a millimeter to a few centimetres.…”
Section: Introductionmentioning
confidence: 99%